BUSINESS-COMMUNITY PARTNERSHIP FOR SECURITY AND PEACEBUILDING IN OIL-PRODUCING COMMUNITIES OF EGBEMA, IMO STATE, NIGERIA (2012)
Oil exploration and production and socio-political stability of Nigeria have for over a decade, been undermined by conflict and insecurity in the oil-producing communities in the Niger Delta region. The potentials for peace-building partnerships between oil-producing communities and oil companies have not been adequately studied. Therefore, this study examined how partnerships between business, especially transnational oil companies and local oil-producing communities may enhance security and peacebuilding in the Niger Delta region. The Communities and Shell Together (CAST) project being implemented in Egbema, Imo State, Nigeria, was used as a case study. The study adopted a survey research design. Interviewer-administered questionnaire was used to obtain data for the study. This was complemented with key informant interviews (KII), non-participant observation and Focus Group Discussions (FGD) with CAST-worker and non CAST-worker residents of the communities, representatives of community-based organisations, non-governmental organisations, and government agencies. Simple random sampling technique was used to select 85% of the 167 CAST-worker residents which yielded 142, and 142 non CAST-worker residents were purposively selected from the 13 Egbema communities. The data were analysed using frequency counts, percentages, and charts. The KIIs and FGDs data were content analysed. The impact of the CAST project on community-company relations, peace, and security in the oil-producing communities was acknowledged as positive. A total of 90.1% of the respondents observed that in the pre-CAST era, the relationship between the communities and Shell Petroleum Development Company (SPDC) was very conflictual, and 93% reckoned that since the inception of CAST, the relationship has been peaceful. Almost all (97.9%) of the respondents noted that before the beginning of CAST, the pipelines and facilities of SPDC were insecure while 77.9% stated that the pipelines and facilities of the company have been very secure since the inception of CAST. The CAST project has brought about the much needed youth employment, better community-company relations, diminished community displeasure about company operations, improved security for SPDC pipelines and facilities, and boosted a sense of belonging among communities. Through its inclusive approach which involves the communities in the design, implementation, and ownership of security, peace-building, and developmental projects, the CAST partnership is enhancing community-company relations, peace, and security in the areas of its implementation. There is an urgent need in the oil-producing communities for developmental programmes that are inclusive in design, implementation, and ownership. Efforts should be geared towards directing the CAST initiative to further foster job creation. Governments, oil companies, and other stakeholders should explore the replication of the CAST model across the whole of the Niger Delta as a means to ensure security and peace in the region.